Arithmetic behaviour of Hecke eigenvalues of Siegel cusp forms of degree two - Gun, Sanoli; Kohnen, Winfried; Paul, Biplab (The Ramanujan journal, 2021)
Let F and G be Siegel cusp forms for Sp4(Z) and weights k1, k2, respectively. Also let F and G be Hecke eigenforms lying in distinct eigen spaces. Further suppose that neither F nor G is a Saito–Kurokawa lift. In this article, we study simultaneous arithmetic behaviour of Hecke eigenvalues of these Hecke eigenforms
Published online: 17 July 2020
Gesehen am 25.05.2021